College Algebra 7th Edition

Published by Brooks Cole
ISBN 10: 1305115546
ISBN 13: 978-1-30511-554-5

Chapter P, Prerequisites - Chapter P Review - Exercises: 40

Answer

$b^{14}$

Work Step by Step

$(a^{2})^{-3}(a^{3}b)^{2}(b^{3})^{4}=a^{-6}*a^{6}*b^{2}*b^{12}=a^{-6+6}*b^{2+12}=1*b^{14}=b^{14}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.